Blood-Cell-Based Inflammatory Markers as a Useful Tool for Early Diagnosis in Colorectal Cancer - Hernandez-Ainsa, Maria; Velamazan, Raul; Lanas, Angel; Carrera-Lasfuentes, Patricia; Piazuelo, Elena (Frontiers in Medicine, 2022)
Systemic inflammation seems to be involved in the pathogenetic pathways of colorectal cancer.Analytical markers that reflect the inflammatory status, such as NLR, PLR or SII, have been proposed as tools for the prognosis of CRC. Nevertheless, their use for diagnosis has been scarcely investigated. To analyze the ability of these markers and of a new marker combining SII and hemoglobin concentration, named NP/LHb = [neutrophils x platelets]/[lymphocytes x hemoglobin], as tools for CRC diagnosis. Furthermore, we studied their association with CRC-related variables. Case-control study including 214 CRC patients and 214 controls without CRC, matched by age (5 years) and sex. We collected demographic, CRC-related and laboratory variables to calculate NLR, PLR, SII and NP/LHb. In the case group, the laboratory variables were collected at two different period times, 6 months (IQR 4-8) before the CRC diagnosis and at the time of the diagnosis. ROC analysis was performed to evaluate the discriminatory accuracy of each index and we calculated Se, Sp, PPV, NPV and OR to identify the diagnostic performance of each positive marker. NP/LHb showed high Sp (92.06%) and PPV (87.50%) to diagnose patients with CRC. This index exhibited an OR of 14.52 (8.26-25.52) and the best area under the curve (AUC: 0.78) for a positive CRC diagnosis. We found significant differences in all indices according to the presence of CRC, observing the highest values in CRC patients at time of diagnosis, in comparison with the analysis performed in the previous months to diagnosis or with control patients. There were significant differences in all ratios according to TNM stages (p<0.05). PLR, SII and NP/LHb (but not NLR) showed significant differences according to tumor location (p<0.05). Right-sided colon cancers presented the highest values, in comparison with left-sided and rectal cancers. Systemic inflammatory cell ratios (especially NP/LHb) change over time with the development of CRC, so they could be useful in its early diagnosis. We suggest that they could be routinely measured in patients with suspicion of CRC, to identify those ones with a higher risk of cancer, considering the high positive predictive value they have shown in our study.